Petrarch's French fortunes: negotiating the relationship between poet, place, and identity in the sixteenth and nineteenth centuries - Rushworth, Jennifer (RELIEF - REVUE ÉLECTRONIQUE DE LITTÉRATURE FRANÇAISE, 2018)
This article reconsiders Petrarch’s French afterlife by juxtaposing a time of long-recognised Petrarchism — the sixteenth century — with a less familiar and more modern Petrarchist age, the late eighteenth and early nineteenth centuries. Of particular interest is how French writers from both periods understand and represent Petrarch’s associations with place. This variously proposed, geographically defined identity is in turn regional (Tuscan/Provençal) and national (Italian/French), located by river (Arno/Sorgue) and city (Florence/Avignon). I argue that sixteenth-century poets stress Petrarch’s foreignness, thereby keeping him at a safe distance, whereas later writers embrace Petrarch as French, drawing the poet closer to (their) home.Cet essai offre une nouvelle interprétation de la réception française de Pétrarque à partir d’une comparaison entre une période de pétrarquisme bien connue — le XVIe siècle — et un âge pétrarquiste moins connu et plus moderne, la fin du XVIIIe et le début du XIXe siècle. Une question s'avère particulièrement intéressante : comment est-ce que les écrivains français de ces périodes comprenaient-ils et représentaient-ils les liens entre Pétrarque et l’espace ? Cette identité est géographique et diversement proposée, à tour de rôle régionale (toscane/provençale) et nationale (italienne/française), située par rapport à un fleuve (l’Arno/la Sorgue) et à une ville (Florence/Avignon). Je soutiens que les poètes du XVIe siècle mettent l’accent sur l’origine étrangère de Pétrarque, le tenant ainsi à distance, tandis que les écrivains ultérieurs adoptent Pétrarque en tant que poète français, le rapprochant de cette manière à eux.